1999
DOI: 10.1046/j.1432-1327.1999.00797.x
|View full text |Cite
|
Sign up to set email alerts
|

N‐terminal and C‐terminal plasma membrane anchoring modulate differently agonist‐induced activation of cytosolic phospholipase A2

Abstract: The 85 kDa cytosolic phospholipase A 2 (cPLA 2 ) plays a key role in liberating arachidonic acid from the sn-2 position of membrane phospholipids. When activated by extracellular stimuli, cPLA 2 undergoes calciumdependent translocation from cytosol to membrane sites which are still a matter of debate. In order to evaluate the effect of plasma membrane association on cPLA 2 activation, we constructed chimeras of cPLA 2 constitutively targeted to the plasma membrane by the N-terminal targeting sequence of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…1). This is in line with a previous report that a chimera of cPLA 2 α constitutively targeted to the plasma membrane by the N‐terminal targeting sequence of the tyrosine kinase Lck leads to increased AA release [19]. Even though the phospholipid compositions of the plasma membrane and the perinuclear membrane may differ significantly, the ability of cPLA 2 α to hydrolyze phospholipids without showing appreciable head group selectivity [20] may permit its equivalent action on both membranes.…”
Section: Discussionsupporting
confidence: 92%
“…1). This is in line with a previous report that a chimera of cPLA 2 α constitutively targeted to the plasma membrane by the N‐terminal targeting sequence of the tyrosine kinase Lck leads to increased AA release [19]. Even though the phospholipid compositions of the plasma membrane and the perinuclear membrane may differ significantly, the ability of cPLA 2 α to hydrolyze phospholipids without showing appreciable head group selectivity [20] may permit its equivalent action on both membranes.…”
Section: Discussionsupporting
confidence: 92%
“…Taking this into consideration, we hypothesized that redirecting tau to distant cellular compartments would inhibit its release from cells, whereas the redirection to the plasma membrane could potentially enhance its secretion. To address this, we generated artificial tau E14 constructs that re-routed the protein to the nucleus or the plasma membrane through nuclear localization (NLS) or plasma membrane targeting signals 51 , respectively (Fig. 4 d).…”
Section: Resultsmentioning
confidence: 99%
“…This would allow access to cell membrane phospholipids for AA release as has been extensively reported on (Dennis, 2000; Balsinde et al, 2002; Dinnes et al, 2005). Previous studies assessing various forms of cell activation have indicated localization of cPLA 2 to the plasma membrane (Durstin et al, 1994; Schievella et al, 1995; Klapisz et al, 1999), nuclear envelope (Fatima et al, 2005), endoplasmic reticulum (Schievella et al, 1995), in addition to the golgi apparatus (Evans and Leslie, 2004).…”
Section: Discussionmentioning
confidence: 99%